2008
DOI: 10.1016/j.pec.2008.05.018
|View full text |Cite
|
Sign up to set email alerts
|

How is shared decision-making defined among African-Americans with diabetes?

Abstract: Objective This study investigates how shared decision-making (SDM) is defined by African-American patients with diabetes, and compares patients’ conceptualization of SDM with the Charles model. Methods We utilized race-concordant interviewers/moderators to conduct in-depth interviews and focus groups among a purposeful sample of African-American patients with diabetes. Each interview/focus group was audio-taped, transcribed verbatim and imported into Atlas.ti software. Coding was done using an iterative proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 29 publications
3
75
0
Order By: Relevance
“…In this paper, we also describe a conceptual model, informed by previous work, 14,19,45,[69][70][71][72][73][74][75][76][77] that demonstrates how social identity, perceptions of social identity, and structural inequities all inform shared decision making between patients and physicians. Expectations for, and the interpretation of, clinical encounters are often influenced by past experiences and normative beliefs about physicians and healthcare deliv- ery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we also describe a conceptual model, informed by previous work, 14,19,45,[69][70][71][72][73][74][75][76][77] that demonstrates how social identity, perceptions of social identity, and structural inequities all inform shared decision making between patients and physicians. Expectations for, and the interpretation of, clinical encounters are often influenced by past experiences and normative beliefs about physicians and healthcare deliv- ery.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Shared decision making, and patient/provider communication, has been associated with a number of positive health outcomes, including control of diabetes and hypertension, adherence to HIV antiretroviral therapy, improved mental health and wellbeing, and patient satisfaction. [21][22][23][24][25][26] Disparities in communication and shared decision making are well-documented among racial/ethnic minorities, particularly African-Americans, [27][28][29][30][31] and there is growing research suggesting similar disparities among sexual and gender minority populations.…”
Section: Shared Decision Making and Patient-centered Carementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in which < 50 % of the participants identified as part of a racial (African American, Asian American), ethnic (Hispanic/Latino), sexual (LGB) or gender (Transgender) minority were excluded. 12,16 Studies with individuals younger than 18 years old were excluded.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…For example, Peek et al explored SDM among African American patients and discovered that information sharing preferences differed significantly from the traditional SDM model among these patients. 12 In addition to differences in preferences for information sharing, some minority populations may have higher rates of Homosexuality OR Bisexuality OR Transgendered Persons OR Transsexualism OR Homosexuality, Female OR Homosexuality, Male homosexual OR homosexuals OR homosexuality OR bisexual OR bisexuals OR bisexuality OR queer OR gay OR transgender OR transgenderism OR transsexual OR transsexuals OR transsexuality OR transsexualism OR "transgendered persons" OR "trans persons" OR "trans people" OR "same sex" OR same-sex OR "transitioned people" OR "transitioned persons" OR lesbian OR lesbians OR lesbianism OR women who have sex with women OR wsw OR men who have sex with men OR msm OR ftm OR "female to male" OR "trans male" OR "trans men" OR transman OR transmen OR mtf OR "male to female" OR "trans women^OR transwoman OR transwomen Abbreviations: MSM = men who have sex with men; WSW = women who have sex with women; FTM = female to male; MTF = male to female low literacy that may require significant modification of material designed to engage patients. 7,13 The most commonly studied intervention to facilitate SDM in clinical practice is the decision aid (DA).…”
Section: Introductionmentioning
confidence: 99%